Bilateral agreement for the academic year 2006-2009 Socrates Programme: Higher Education Erasmus between Universidade Lusíada de Lisboa and Universidad de Castilla-La Mancha - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP programme. - Subject area: Law, Others law.